Industrial Applications of Affective Engineering - Watada, Junzo.; Watada, Junzo.; Shiizuka, Hisao.; Shiizuka, Hisao.; Lee, Kun-Pyo.; Lee, Kun-Pyo.; Otani, Tsuyoshi.; Otani, Tsuyoshi.; Lim, Chee-Peng.; Lim, Chee-Peng. (Springer International Publishing : Imprint: Springer, 2014)
This book examines the industrial applications of affective engineering. The contributors cover new analytical methods such as fluctuation, fuzzy logic, fractals, and complex systems. These chapters also include interdisciplinary research that traverses a wide range of fields, including information engineering, human engineering, cognitive science, psychology, and design studies. The text is split into two parts: theory and applications. This work is a collection of the best papers from ISAE2013 (International Symposium of Affective Engineering) held at Kitakyushu, Japan and Japan Kansei Engineering Meeting on March 6-8, 2013.